ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS PADA TENAGA KERJA (Studi Kasus CV. Agro Bintang Terang Desa Trimo Kecamatan Gedangan Turen Kabupaten Malang) - Prasetyo, Alfi Prasetyo.pdf; nu, Arma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Productivity is a term in the production activity as the ratio between output (output) to the input (input). According Herjanto, productivity is a measure that expresses how well resources are organized and utilized to achieve optimal results. Productivity can be used as a measure of success of an industry or SMEs in producing goods or services. So the higher the ratio, the higher the mean product. Productivity measures can vary, depending on the aspects of output or input that is used as an aggregate basis, for example: index of labor productivity, the productivity of the direct costs, the total cost productivity, energy productivity, the productivity of raw materials, and others. Labor is the population that is of working age. According to Law No. 13, 2003 Chapter I Article 1, paragraph 2 states that labor is any person who is able to do the work in order to produce goods and services to meet the needs of both themselves and for society. Broadly speaking, the population of a country divided into two groups, namely labor and not labor. Population classified labor if the resident has entered working age. The applicable limit of working age in Indonesia is 15 years old - 64 years. According to this definition, every person who is able to work as a so-called labor. There are many opinions regarding the age of the workforce is, there is mention in the top 17 there is a mention over 20 years, and some have mentioned above 7 years because street children are inclusive workforce. Wages are the price for which remuneration is given one person to another. Remuneration for labor in the production activity is basically a reward / remuneration from the producer to the labor of his achievement that has been donated in the production activities. From this definition shows that the existence of wages in an organization can not be ignored and becomes very important. Because a factor related to achieving the goals of the company. If the company pays are not in accordance with the performance of its employees then it can not be justified, both human and continuity of the company. Age of the workforce is a productive age for each individual. Productive age in which every individual has been able to provide services to other individuals. Age for employment at this company is between 20 to 40 years. Age is considered to be very productive for the workforce. This study uses multiple linear regression were used to determine whether there is a variable wages, hours of work, and age, affect the production of the labor force on the CV. Bright Star Agro Rural District of Trimo Gedangan Turen Malang and variable whether the dominant influence on labor productivity in CV. Bright Star Agro Rural District of Trimo Gedangan Turen Malang Keywords: Productivity, Employment, Wages, Hours of Work, Age, Multiple Linear Regression